축산시설 내 무창기공형 집열기 냉방효과 구현을 위한 배기 유량 변화에 따른 열성능 평가 - 문병은; 이건호; 바삭 쿠마르 자얀타; 엘란체쟌 아룰모지; 뎁 찬드라 니바스; 서은완; 김혁주; 김현태; Byeong Eun Moon; Gun Ho Lee; Jayanta Kumar Basak; Arulmozhi Elanchezhian; et al. (농업생명과학연구, 2024)
본 연구는 축산시설 내 설치된 무창기공형 집열기의 배기 방향 및 유량 변화를 통해 벽체에 전달되는 일사를 차단, 이를 통한 냉방효과를 검증하려는 목적의 기초 연구로서 무창기공형 집열기 시험장치를 제작, 배기 유량 변화에 따른 위치별 온도 변화 및 이를 통한 열성능 평가를 수행하였다. 실험 결과, 무창기공형 집열기의 유량조건별 집열판 표면온도는 최고 27.7℃, 배기온도는 최고 약 10.9℃ 온도 차이를 확인하였다. 무창기공형 집열기의 유량조건별 열교환 유효도는 0.48∼0.62, 효율은 30%∼90%의 분포로 나타났다. 집열판 에너지는 유량이 증가함에 따라 감소, 집열기 내부 에너지는 유량이 증가함에 따라 증가하였다. 이를 통해 농업시설 외벽에 설치된 무창기공형 집열기의 여름철 미운용으로 인한 집열판 및 내부 온도상승과 이로 인한 벽체로의 열전달 등 무창기공형 집열기로 인한 역효과를 방지할 수 있을 뿐만 아니라 집열기 외부로의 강제 배기를 통해 벽체로 직접 투입되는 일사 차단을 통한 냉방효과 또한 구현할 수 있을 것으로 판단된다. This study verified the cooling effect by blocking the solar radiation transmitted to the wall through the change in the exhaust direction and airflow rate of the unglazed transpired collector installed in the livestock facility. As a basic study, an unglazed transpired collector experimental device was constructed, and the temperature change and thermal performance of the unglazed transpired collector according to the change in exhaust airflow rate were evaluated. As a result of the experiment, the surface temperature of the absorber plate for each airflow rate condition of the unglazed transpired collector was 27.7℃ at the maximum, and the maximum temperature difference was about 10.9℃ for the exhaust temperature. The heat exchange effectiveness for each airflow rate condition of the unglazed transpired collector was 0.48 to 0.62, and the efficiency was 30 to 90%. The absorber plate energy of the collector decreased as the airflow rate increased, and the internal energy of the plenum increased as the airflow rate increased. Through this results, it is possible to prevent adverse effects caused by the unglazed transpired collector, such as heat transfer to the wall due to the increase temperature of the absorber plate and the plenum by the non-use of the unglazed transpired collector installed on the outer wall of the livestock facility in summer season. In addition, a cooling effect can be realized by blocking direct solar radiation through forced exhaust to the outside of the unglazed transpired collector.